Empire of the seas thinking about Asia - Shiraishi, Takashi 1950-; Nihon Kokusai Mondai Kenkyu?jo; Shuppan Bunka Sangyo? Shinko? Zaidan (2021)
"Winner of the 2000 Yomiuri Yoshino Sakuzo Prize for academic writing on politics, economics, and history, this book locates the modern history of Sotheast Asia within the framework of a 'maritime Asia' which emerged from trade and commerce, state formation, imperial/global hegemonic ambitions, and popular resistance."
Raffle's dream -- The Bugis Sea -- Toddling Leviathans -- The formation of plural societies -- The logic of the civilizing project -- The new imperial order -- Nation-state building from above -- Thinking about Asia -- Afterword -- Addendum: 2020.
"Originally published in 2000 under the Japanese title Umi no teikoku : Ajia o do? kangaeru ka by Chuokoron-Shinsha, Inc."--Title page verso.
Translation of: Umi no teikoku : Ajia o do? kangaeru ka.
Includes bibliographical references (pages 169-175) and index.
Keywords: Regionalism -- East Asia; Regionalism -- Southeast Asia; Colonies -- Asia; East Asia -- History -- 19th century; East Asia -- History -- 20th century; Southeast Asia -- History -- 19th century; Southeast Asia -- History -- 20th century